Analisis Beban Kerja, Disiplin Kerja dan Budaya Kerja terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening : (Studi Kasus PT Kido Mulia Indonesia) - Khalimatul Laeliah; Slamet Bambang Riono; Ari Kristiana; Hendri Sucipto (BADAN PENERBIT STIEPARI PRESS, 2025)
Low employee performance often hinders organizational goals. This issue is suspected to be influenced by factors such as workload, work discipline, work culture, and job satisfaction. This study aims to analyze the effects of workload, work discipline, and work culture on employee performance, as well as the role of job satisfaction as a mediating variable. Using a quantitative descriptive survey method and SEM-PLS analysis on 91 employees of PT Kido Mulia Indonesia, the results show that workload (coefficient = 0.252; t = 2.300; p = 0.022), work discipline (0.238; t = 2.538; p = 0.011), and work culture (0.350; t = 3.663; p = 0.000) have a significant positive effect on employee performance. These variables also significantly influence job satisfaction, with workload (0.415; t = 3.617; p = 0.000), work discipline (0.298; t = 3.852; p = 0.000), and work culture (0.300; t = 4.183; p = 0.000). Job satisfaction has a significant positive effect on employee performance (0.646; t = 3.047; p = 0.002) and mediates the effects of work discipline and work culture on performance. These findings highlight the importance of managing workload, discipline, culture, and job satisfaction to improve employee performance.